Application of a biofilm-enhanced A2O system in the treatment of wastewater from mariculture - Ma, Xiaona; Yin, Rui; Yang, Chen; Cai, Chen; Zhao, Jufan; Lv, Chuxiu; Wang, Xinchen; Chen, Shiyu; Ren, Jilong; Zhang, Bingzhi (Frontiers in Marine Science, 2024)
Development of environment-friendly and efficient aquaculture effluent treatment system is crucial for sustainable intensification of aquaculture, in the face of the rapidly increasing environmental pressure in the mariculture industry. In this study, mariculture wastewater was treated by the anoxic-anaerobic-oxic biochemical treatment system (A2O system) with traditional activated sludge replaced by nitrifying bacteria, denitrification bacteria and phosphorus accumulating bacteria absorbed on PBS carrier biofilms suitable for saline/brackish water. The results showed that biofilm-enhanced A2O system can effectively remove pollutants from aquaculture wastewater. The removal efficiencies of CODMn, NH4+-N, TN and TP in A2O system were approximately 86.3%-90.8%, 97.7%-99.5%, 94.6%-95.2% and 97.0%-98.1%. The results further showed that CODMn, NH4+-N, and TN were mainly removed in anaerobic tank and anoxic tank, while TP was mainly removed in the anoxic tank and oxic tank. The biofilm-enhanced A2O system by adding nitrifying bacteria and phosphorus accumulating bacteria biofilms using PBS as carriers instead of conventional activated sludge could be applied to the treatment of circulating aquaculture wastewater. This study provides a feasible scheme for enhancing the efficiency of A2O system in the treatment of aquaculture tail water, and provides a reference for the immobilization of microorganisms.